Design and Crash Test on a Two-Passenger City Car Frame using Finite Element Method - Randi Purnama Putra; Dori Yuvenda; Wanda Afnison; Remon Lapisa; Milana Milana; Anna Niska Fauza; Dani Harmanto (Automotive Experiences, 2024)
The chassis is an important part of a car which must have a strong construction to withstand the weight of the vehicle. The purpose of this research is to create a city car's chassis that can hold two passengers and then crash-test the finished product. In this research, a development method was used using SolidWorks software and the student version of ANSYS R2 2023 as software for creating chassis designs and crash test simulations. The study's findings indicate that the car frame's measurements are 2.46 meters in length, 1.33 meters in height, and 1.39 meters in width. The steel of the ASTM A36 type was utilized as the material in the computational study of the frame. The results show that increasing speed causes an increase in deformation, with the peak deformation at a speed of 100 km/h. The maximum deformation occurs at 0.007 seconds with a value of 203.51 mm at the top pillar of the car. The deformation increases from 97.196 mm at 0.0035 s to 161.22 mm at 0.0056 s. However, deformation occurs mainly in the front zone of the car frame and is not significant in the passenger zone.